EFFECT OF THE STRATEGIC ORIENTATION IN STRATEGIC AMBIDEXTERITY THROUGH THE MEDIATING ROLE OF STRATEGIC CLARITY : AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF EMPLOYEES IN GOVERNMENT BANKS IN MAYSAN GOVERNORATE (World Economics and Finance Bulletin, 2025)
This study focuses on examining strategic orientation within the context of strategic ambidexterity, emphasizing the mediating influence of strategic clarity. Its primary goal is to develop an integrated theoretical framework addressing key issues highlighted by scholars and researchers concerning these variables. It also gives an analysis based on feedback from a group of employees who work in government banks in the Maysan Governorate. The sample comprised 130 employees out of a total of 150 working in these institutions. Data collection was carried out using a questionnaire, which was subsequently analyzed through various statistical methods with the assistance of the Smart PLS software. The findings confirmed the validity of the study's hypothesis, demonstrating significant relationships among the examined variables. Based on these results, the study proposed several recommendations, particularly emphasizing the importance for leaders in government banks to prioritize strategic orientation as a critical factor in achieving long-term strategic goals effectively.